Dietary supplementation with Epimedium contributes to the improvement of hormone levels, gut microbiota, and serum metabolite composition in the Chinese forest musk deer (Moschus berezovskii) - Shan Xie; Shan Xie; Qinlin Yang; Zaixiang Ying; Zaixiang Ying; Mingcheng Cai; Wenqiao Fan; Hanyu Gao; Hanyu Gao; Xiaolan Feng; Yongjiang Wu (Frontiers in Veterinary Science)
The Chinese forest musk deer (Moschus berezovskii) is a small ruminant animal with special economic value. It is listed as a National Level I key protected species in China. However, these animals are prone to stress responses in captive environments. Epimedium, a traditional Chinese herb with aphrodisiac and anti-stress properties, may have potential benefits for the health of the captive Chinese forest musk deer, though its efficacy requires further investigation. This study aimed to evaluate the effects of dietary supplementation with Epimedium on the hormone levels, gut microbiota composition, and serum metabolism of the Chinese forest musk deer. The fourteen adult male Chinese forest musk deer with similar initial body weights (7.0 ± 0.3 kg) and an average age of 4.5 years were randomly divided into two groups, each containing seven animals. The control group was fed a standard diet without Epimedium, while the Epimedium group received the standard diet supplemented with 15 g Epimedium /kg DM. The results indicated that the inclusion of Epimedium in the diet increased dry matter intake (DMI) and improved the ratio of feed to gain (F/G), with an increase in fecal testosterone levels (p < 0.05). 16S rDNA sequencing analysis revealed that Epimedium enhanced the richness and diversity of the gut microbiota in the Chinese forest musk deer, increasing the relative abundance of beneficial bacteria such as Firmicutes, while reducing the relative abundance of the potentially pathogenic Proteobacteria (p < 0.05). A widely targeted metabolomics analysis identified 25 differential metabolites between the two groups. Significant alterations were observed in key metabolic pathways related to lipid metabolism, hormone regulation, and antioxidation, such as ovarian steroidogenesis, tyrosine metabolism, and glycerophospholipid metabolism. Furthermore, correlation analysis between gut microbiota and serum differential metabolites showed that the relative abundances of Clostridia_vadinBB60_group and UCG-010 were positively correlated with anserine and 7-ketocholesterol, respectively (p < 0.05). In conclusion, Epimedium positively influenced feed intake and hormone levels in the Chinese forest musk deer by modulating gut microbiota composition and serum metabolism.